2013
DOI: 10.1093/mnrasl/sls039
|View full text |Cite
|
Sign up to set email alerts
|

Unusual displacement of H i due to tidal interaction in Arp 181

Abstract: We present results from GMRT Hi 21 cm line observations of the interacting galaxy pair Arp 181 (NGC 3212 and NGC 3215) at z =0.032. We find almost all of the detected Hi (90%) displaced well beyond the optical disks of the pair with the highest density Hi located ∼70 kpc west of the pair. An Hi bridge extending between the optical pair and the bulk of the Hi together with their Hi deficiencies provide strong evidence that the interaction between the pair has removed most of their Hi to THE current projected p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…Accepting the limitations of claims that can be made using the currently available data, we find that the Arp 305 Bridge TDG differs from our previous TDG H i detections in Arp 202 and Arp 181 (Sengupta et al 2014(Sengupta et al , 2013 in having Spitzer 3.6 µm and 4.5 µm counterparts, indicative of an old stellar component. Additionally, Arp 305 TDG has strong UV emission indicating recent SF.…”
Section: Arp 305 Bridge Tdg Candidatecontrasting
confidence: 81%
“…Accepting the limitations of claims that can be made using the currently available data, we find that the Arp 305 Bridge TDG differs from our previous TDG H i detections in Arp 202 and Arp 181 (Sengupta et al 2014(Sengupta et al , 2013 in having Spitzer 3.6 µm and 4.5 µm counterparts, indicative of an old stellar component. Additionally, Arp 305 TDG has strong UV emission indicating recent SF.…”
Section: Arp 305 Bridge Tdg Candidatecontrasting
confidence: 81%
“…Arp 65 belongs to a small number of galaxy pairs where the highest density H i is observed beyond the optical disks of the pair following an interaction (e.g. Hibbard & van Gorkom 1996;Sengupta et al 2013). We found that NGC 90 has extended on-going star formation in the outer optical disk, most likely triggered by interaction.…”
Section: Star Formation In the Tidal Debrismentioning
confidence: 68%
“…Some other examples are NGC 3921 (Hibbard & van Gorkom 1996), Arp 105 (Duc et al 1997) and Arp 181 (Sengupta et al 2013). • and inclination = 34.5…”
Section: Evidence Of An Interaction Between Ngc 90 and Ngc 93mentioning
confidence: 99%
“…Other details are per Figure A1. large fractions of an interacting pair's H i beyond their optical disks (Sengupta et al 2013(Sengupta et al , 2015, but in this case the companion is much less massive and the ∼800 km s −1 velocity separation (Consolandi et al 2017) suggests a high velocity low impact encounter.…”
Section: Discussionmentioning
confidence: 96%